The green tiger the costs of ecological decline in the Philippines - Goldoftas, Barbara (Oxford University Press, 2006)
'The Green Tiger' offers an unusually close look at the consequences of ecological decline and determined efforts to reverse them. It argues that, rather than destroying a natural resource base, development should integrate conservational and economic growth.